Factors influencing cloud computing adoption in higher education institution - Wan Abdul Rahim Wan Mohd Isa; Ahmad Iqbal Hakim Suhaimi; Nurulhuda Noordin; Afdallyna Fathiyah Harun; Juhaida Ismail; Rosshidayu Awang Teh (Institute of Advanced Engineering and Science, 2020)
There are few studies on factors influencing cloud computing adoption in higher education institutions. However, there are lacks of understanding of the cloud computing adoption issues in the university. The main objective of this study is to investigate factors influencing cloud computing adoption in a higher education institution. The research method involved using qualitative interviewing with relevant stakeholders and case study at one public university in Malaysia. The analysis was done by using Atlat.ti. There are eighteen factors that have been coded into three main categories of Technological, Organizational and Environmental. These are among factors to influence the decision of cloud computing adoption for a public university. The first category (Technological) consists of nine factors; (i) relative advantage, (ii) cost reduction, (iii) ease of use, (iv) compatibility, (v) operational requirement, (vi) security, (vii) sustainability, (viii) trialability and (ix) complexity, The second category (organizational) consists of four factors; (i) infrastructure readiness, (ii) top management, (iii) knowledge and IT skillset and (iv) financial. The third category (environmental) consists of five factors; (i) Cloud Service Provider, (ii) Geographical, (iii) Data Privacy, (iv) Guideline and Policy, (v) Service Level Agreement (SLA). The result may provide a reference for the adoption of cloud computing in the area of mobile learning or mobile computing. Future work involves conducting similar studies at other case studies including public and private universities in Malaysia.